Crop Water Use and Irrigation Scheduling Guide for North Florida - Thomas Obreza (EDIS)
Revised! SL-278, an 18-page illustrated guide by Thomas Obreza, presents average daily water use for 13 North Florida crops that can be used to help schedule irrigation. Published by the UF Department of Soil and Water Science, December 2008. Revised January 2009.